The effect of population size on adaptation to fluctuating temperatures - Nieminen, Veera (2023)
Climate change increases variation in environmental conditions and reduces the population sizes of many species, thus making evolutionary adaptation more difficult. According to the general theory, evolutionary adaptation to one environment weakens the adaptation to alternative environments due to antagonistically pleiotropic alleles. However, antagonistic pleiotropy is rarely observed in experiments. A new theory has been put forward to explain this paradox, stating that the interplay of environmental variation and population size can affect the detection of fitness trade-offs. Based on this, larger populations may adapt faster to fluctuating environments than smaller populations and are able to avoid fitness costs between environments. We wanted to evaluate whether large populations adapt more efficiently to fluctuating temperatures than small populations. We did an evolution experiment with fission yeast (Schizosaccharomyces pombe), where strains evolved for 500 generations at constant and fluctuating temperatures. Evolved strains competed against ancestral strains in temperatures that matched the conditions during evolution to detect possible adaptations and in alternative environments to detect trade-offs. We did not find evidence for the interaction of environmental variation and population size. Population size did not affect adaptation to temperature fluctuations, and no trade-offs were observed. One possible explanation for the results is that temperature adaptation requires a lot of time and genetic evolution.